2018
DOI: 10.1080/02614367.2018.1455891
|View full text |Cite
|
Sign up to set email alerts
|

Khat-chewing in liminal leisure spaces: British-Somali youth on the margins

Abstract: Khat-chewing, a controversial leisure activity within the Somali diaspora in Britain, has received little attention within the academic field of Leisure Studies. This paper reports on ethnographic research to provide insights into the unique locations where young British-Somali men chew khat, exposing the liminal qualities of such localities. The paper begins with an overview of the contentious position khat-chewing occupies within Somali communities in Britain, highlighting reasons why young British-Somali me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Based on both nostalgic consumption and national identity, diasporas increase the demand for products and services with country of origin specificity (i.e. the country of origin effect on customers' purchases) that also reflect cultural belongingness (Abdallah et al, 2019;Holak, 2014;Sirkeci and Zeren, 2018;Swain et al, 2018). At the same time, diaspora' members can exhibit dual cultural identity attributes of both their origin and host cultures.…”
Section: The Diaspora Phenomenonmentioning
confidence: 99%
“…Based on both nostalgic consumption and national identity, diasporas increase the demand for products and services with country of origin specificity (i.e. the country of origin effect on customers' purchases) that also reflect cultural belongingness (Abdallah et al, 2019;Holak, 2014;Sirkeci and Zeren, 2018;Swain et al, 2018). At the same time, diaspora' members can exhibit dual cultural identity attributes of both their origin and host cultures.…”
Section: The Diaspora Phenomenonmentioning
confidence: 99%
“…Bauman, liquid modernity and leisure are also found in recent work I have published with Swain and Lashua, based partly on Swain's PhD research(Swain, Spracklen and Lashua 2018). That paper uses khat-chewing among British-Somali youth as an example of a reaction against the anomie of liquid modernity.…”
mentioning
confidence: 80%
“…British-Somali young men have been reported to use miraa that offers them a sense of cultural identity and belonging that is done in great secrecy and for leisure practices, [26]. A study among Somali refugees living in Nairobi indicated a high level of Post Traumatic Stress Disorder (PTSD) symptoms among those who frequently used miraa, [27].…”
Section: Importance Of Prevalence Of Miraa Use Among Somali Youthmentioning
confidence: 99%